Meningkatkan Kemampuan Kognitif Mengenal Bentuk Geometri Melalui Media Bahan Alam Batu Pelangi - Winda Widyaningtyas; Destita Shari; Nanang Rokhman Saleh; Berda Asmara (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
Cognitive development is the basis for a child's ability to think such as skills and understand what happens in his environment. This study aims to improve cognitive abilities in recognizing geometric shapes through the natural material media of rainbow stones in child B at PPT Tunas Bangsa City Surabaya. This Classroom Action Research consists of 2 cycles, each cycle consisting of 4 stages: Planning, Action, Observation, and Reflection. The subjects of this study were 24 children of PPT Tunas Bangsa. Data collection techniques using observation and documentation. The results of the research in the first cycle showed a cognitive development of 55.83% and in the second cycle research showed a cognitive development of 83.3% with the achievement of the criteria for BSB (Very Good Development). Based on the results of the research that has been done, it can be concluded that the natural material media of rainbow stone can improve cognitive abilities to recognize geometric shapes in children aged 3-4 years at PPT Tunas Bangsa Surabaya.